Rupture of vesicourethral anastomosis following radical retropubic prostatectomy - Dall'oglio, Marcos [UNIFESP] (2003)
OBJECTIVE: Rupture of vesicourethral anastomosis following radical retropubic prostatectomy is a complication that requires immediate management. We evaluated the morbidity of this rare complication. MATERIALS AND METHODS: We analyzed retrospectively 5 cases of disruption of vesicourethral anastomosis during post-operative period in a consecutive series of 1,600 radical retropubic prostatectomies, performed by a single surgeon. RESULTS: It occurred in a ratio of 1:320 prostatectomies (0,3%). Management was conservative in all the cases with an average catheter permanence time of 28 days, being its removal preceded by cystography. Two cases were secondary to bleeding, 1 followed the change of vesical catheter and 2 by unknown causes after removing the Foley catheter. Only one patient evolved with urethral stenosis, in the period ranging from 6 to 120 months. CONCLUSION: Rupture of vesicourethral anastomosis is not related to the surgeon's experience, and conservative treatment has shown to be effective.